Penerapan Arsitektur Hijau pada Fasilitas Publik Perkotaan (Studi Kasus Perpustakaan Bank Indonesia Surabaya) - Efrata Pramita Ngole; Azkia Avenzoar (Institut Teknologi Adhi Tama Surabaya, 2026)
Rapid urban growth necessitates an approach to building design that is not only functional and aesthetic, but also ecologically sustainable. Green architecture emerges as a design strategy that integrates energy efficiency, adaptation to local climate, and preservation of the surrounding environment. Libraries, as public facilities, have great potential to apply green architecture principles as part of community sustainability education efforts. This study aims to analyze the application of green architecture principles at the Bank Indonesia Library in Surabaya, using a qualitative descriptive approach and precedent study methods. The analysis is based on Steffen Lehmann's (2016) theory of Climate-Responsive Urban Design, which includes six main principles: adaptation to local climate, density and connectivity, green space, circulation metabolism, flexible design, and climate-sensitive water management. The results of the study indicate that all of these principles have been effectively implemented through passive design, space efficiency, vegetation utilization, adaptive reuse of buildings, functional flexibility of spaces, and sustainable water management strategies. This study demonstrates that the application of green architecture principles in urban public facilities can contribute to environmental sustainability while enhancing the comfort and social functionality of spaces.